The evaluation of eye movement in usability study / Noor Hanisah Mohd Mohiyeddin - Mohd Mohiyeddin, Noor Hanisah (2011)
Nowadays, website being famous medium to spread news, bisness and many more. The usability study about eye movement so related to the website. The limited study make developers lake of knowledge to designing the website. In this research, it will explain about the measurement of eye movement, and also usability study. All the important term are included in this research. By using Tobii Eye Tracking Device, developer can detect the focus point of user while visit their website. In this research, it using heatmap to analyze the end of the result.